New approach in the theory of microstrip waveguides - DANICKI, E. (Archives of Acoustics, 1990)
In literature, the Galerkin’s method is usually applied in analysis of microstrip waveguides and couplers. Below, a new method is proposed that is a generalization of one developed previously for analysis of SAW waveguides [1] to the electromagnetic case. The proposed approach exploits some identities fulfilling by Fourier series which coefficients are expressed by Legendre functions.